SUSTAINABLE TOURISM ON MENJANGAN ISLAND, WEST BULELENG - Putu Agita Hary Devianti (Ride: Journal of Cultural Tourism and Religious Studies, 2023)
Bali is one of the barometers of international tourism destinations in Indonesia and every year it always brings in quite a large number of tourists, both domestic and foreign tourists, having a small island in West Buleleng called Menjangan Island. The island, which is still within the West Bali National Park area, looks like it hasn't developed optimally. So it is necessary to do a re-assessment using the elaboration of several aspects of sustainable tourism that are in accordance with the development of Menjangan Island itself, such as from economic, sociocultural and ecological aspects